Correlates of condom use in a sample of MSM in Ecuador - Samuels Fiona; Morrison Ken; Molina-Yepez Diana; Gutiérrez Juan-Pablo; Bertozzi Stefano M (BMC, 2006)
Abstract Background In Ecuador, the prevalence of HIV in the general population is approximately 0.3%. However, up to 17% prevalence has been reported among specific groups of homosexual and bisexual men. The objective of this study is to explore correlates of condom use among men who have sex with men (MSM) across eight cities in Ecuador. Methods A cross-sectional survey design was used. A questionnaire including variables on sexual behaviour, demographics, and socio-economic characteristics was distributed to a sample of MSM in eight Ecuadorian cities. Results Information was obtained for 2,594 MSM across the eight cities. The largest subcategory of self-identification was active bisexuals (35%), followed by those who described themselves as "hombrados" (masculine gays, 22%). The mean age was 25 years, and the majority were unmarried (78%), with a median of 10 years of schooling (IQR 7 - 12). Regarding condom use, 55% of those interviewed had unprotected penetrative sex with each of their last three partners, and almost 25% had never used a condom. The most important correlates of condom use were single status, high life-skills rating, and high socio-economic status (RP 5.45, 95% CI 4.26 - 6.37; RP 1.84, 95% CI 1.79 - 1.86, and RP 1.20, 95% CI 1.01 - 1.31, respectively). Conclusion Our data illustrate the urgent need for targeted HIV-prevention programs for MSM populations in Ecuador. MSM have the highest HIV prevalence in the country, and condom use is extremely low. It is imperative that prevention strategies be re-evaluated and re-prioritized to more effectively respond to the Ecuadorian epidemic.